If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 3) = 6y + 22 Reorder the terms: 4(3 + y) = 6y + 22 (3 * 4 + y * 4) = 6y + 22 (12 + 4y) = 6y + 22 Reorder the terms: 12 + 4y = 22 + 6y Solving 12 + 4y = 22 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 12 + 4y + -6y = 22 + 6y + -6y Combine like terms: 4y + -6y = -2y 12 + -2y = 22 + 6y + -6y Combine like terms: 6y + -6y = 0 12 + -2y = 22 + 0 12 + -2y = 22 Add '-12' to each side of the equation. 12 + -12 + -2y = 22 + -12 Combine like terms: 12 + -12 = 0 0 + -2y = 22 + -12 -2y = 22 + -12 Combine like terms: 22 + -12 = 10 -2y = 10 Divide each side by '-2'. y = -5 Simplifying y = -5
| x^2+6x=23 | | 20x^2+23x-21=0 | | (3x^4-5x^3-2x)+(6x^4-7x)= | | r^2+9t=-20 | | 15m-9=36 | | x-7.8=-3.6 | | 8(8-4x)-5=26+x | | -5x^2-13x-6=0 | | 4f-9=15+8f | | m+22=15 | | (-3d^2-8+2d)+(4d-12+d^2)= | | m^2=90 | | 64x^2-16x=0 | | 5x^3+35x^2+5x+35=0 | | 38.8-9.7t=-67.9 | | 4b-5(7b+1)=-8b-28 | | 2a^2-9a+4=0 | | (u-8)(u+3)= | | 2(-1-9y)+4y=5 | | 18x^2-84x+98= | | 6(4x-7)=3(8x+8) | | 10n^2-4=506 | | 4+18r-2=9r+98-3r | | 159-4x=41x+14 | | 2x^3+5x^2-3x+5=0 | | 10-9x=23-16x | | x+(x-8)=60 | | 6y+4y=90 | | (8y-4y^2)+(3y-9y^2)= | | (0.5*x^2)-(1.5*x)=0.375 | | (0.5*x^2)-(1.5*x)-0.375=x | | q^2+2q=1 |